FoMO-Driven Consumptive Lifestyle in Fashion: A Maslahah Perspective Among Female Students - Lusy Annisya; Umi Julaihah; Nur Asnawi; Meldona Meldona (Jurnal Psikologi Teori dan Terapan, 2025)
Background: The Fear of Missing Out (FoMO) phenomenon has contributed to the rise of a consumptive lifestyle among female college students, particularly in fashion. Objective: This study aims to analyze how social media, economic conditions, brand credibility, and accessibility influence students’ consumerist behavior and how the Islamic concept of maslahah can guide consumption control. Method: A qualitative method was employed through in-depth interviews with twelve hijabi students from a state university in Malang. Thematic analysis followed Braun & Clarke’s framework with ethical clearance, member checking to ensure data validity. Results: Social media plays a significant role in creating social pressure to follow trends, but spiritual values and economic considerations act as balancing factors in consumption decisions. The ease of access to shopping and brand image further reinforce consumerist behavior, but people who incorporate the principle of maslahah could limit extravagant lifestyles. Conclusion: The study confirms the role of religious and psychological values in fashion consumption, as well as the importance of Islamic consumption education and financial literacy in higher education to shape balanced consumptive behavior. Abstrak Latar Belakang: Fenomena Fear of Missing Out (FoMO) telah berkontribusi pada meningkatnya gaya hidup konsumtif di kalangan mahasiswi perguruan tinggi, terutama dalam bidang fashion. Tujuan: Studi ini bertujuan untuk menganalisis bagaimana media sosial, kondisi ekonomi, kredibilitas merek, dan aksesibilitas memengaruhi perilaku konsumtif mahasiswa, serta bagaimana konsep Islam tentang maslahah dapat menjadi panduan dalam mengontrol konsumsi. Metode: Metode kualitatif digunakan melalui wawancara mendalam dengan dua belas mahasiswi berhijab dari universitas negeri di Malang. Analisis tematik mengikuti kerangka kerja Braun & Clarke dengan persetujuan etis dan verifikasi anggota untuk memastikan validitas data. Hasil: Media sosial memainkan peran penting dalam menciptakan tekanan sosial untuk mengikuti tren, namun nilai spiritual dan pertimbangan ekonomi menjadi faktor penyeimbang dalam pengambilan keputusan konsumsi. Kemudahan akses belanja dan citra merek turut memperkuat perilaku konsumtif, tetapi penanaman prinsip maslahah dapat membatasi gaya hidup boros. Simpulan: Studi menegaskan peran nilai religius dan psikologis dalam konsumsi fashion, serta pentingnya edukasi konsumsi Islami dan literasi keuangan di perguruan tinggi untuk membentuk perilaku konsumtif yang seimbang.